Genetic variation between several species of sections Extranervosae, Caulorrhizae, Heteranthae, and Triseminatae (genus Arachis) estimated by DNA polymorphism - Galgaro, Leticia [UNESP]; Lopes, Catalina Romero [UNESP]; Gimenes, Marcos [UNESP]; Valls, José F.M.; Kochert, Gary (Canadian Science Publishing, 1998)
Genetic variation within and among accessions of the genus Arachis representing sections Extranervosae, Caulorrhizae, Heteranthae, and Triseminatae was evaluated using RFLP and RAPD markers. RAPD markers revealed a higher level of genetic diversity than did RFLP markers, both within and among the species evaluated. Phenograms based on various band-matching algorithms revealed three major clusters of similarity among the sections evaluated. The first group included the species from section Extranervosae, the second group consisted of sections Triseminatae, Caulorrhizae, and Heteranthae, and the third group consisted of one accession of Arachis hypogaea, which had been included as a representative of section Arachis. The phenograms obtained from the RAPD and RFLP data were similar but not identical. Arachis pietrarellii, assayed only by RAPD, showed a high degree of genetic similarity with Arachis villosulicarpa. This observation supported the hypothesis that these two species are closely related. It was also shown that accession V 7786, previously considered to be Arachis sp. aff. pietrarellii, and assayed using both RFLPs and RAPDs, was possibly a new species from section Extranervosae, but very distinct from A. pietrarellii.
Keywords: Arachis; Genetic distance; Genetic similarity; RAPD; RFLP; DNA polymorphism; genetic variance; peanut; random amplified polymorphic DNA; restriction fragment length polymorphism